Essential business process modeling - Harvey, Michael (Theory in practice, 2005)
Ten years ago, groupware bundled with email and calendar applications helped track the flow of work from person to person within an organization. Workflow in today's enterprise means more monitoring and orchestrating massive systems. A new technology called Business Process Management, or BPM, helps software architects and developers design, code, run, administer, and monitor complex network-based business processesBPM replaces those sketchy flowchart diagrams that business analysts draw on whiteboards with a precise model that uses standard graphical and XML representations, and an architectu.